The Practical-Technical Reason in the Aristotelian Concept of the Faculties of the Soul - Mathiesen, Aleksandra (Peitho. Examina Antiqua, 2017)
When analyzing the structure of the soul, Aristotle distinguished three faculties: the theoretical, the practical and the technical one. The latter two are the focus of this paper. The division could be perceived as an abstract description of diverse functions and purposes of the faculties, but it does not imply factual dissociation between them if we take under consideration their functioning. On the contrary, Aristotle suggested that it would be impossible to detach the practical reasoning from the operational one, for the former stipulated the goal, whereas the latter provided the means for its fulfillment. The genuine intellectual disposition, which supplements the practical reason with the proper means was referred to as ‘cleverness’ (δεινότης). Cleverness has usually been associated with the technical faculty but it also seems to be, first and foremost, the disposition to inventiveness in a broader sense. Although Aristotle did not formulate this directly, it is plausible to view the practical and technical faculty as depending on each other, as far as their products and works are useful to pursue the practical goals and the practical reasoning determines the extent of the possibilities and limitations of their utility in the field of politics. The disposition to cleverness made the cooperation of those faculties possible.